1977
DOI: 10.1159/000136664
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic, Heart Rate, and Temperature Effects of &Delta;<sup>8</sup>-THC during Acute and Chronic Administration to Conscious Rats

Abstract: Acute and chronic effects of △8-THC on tail-flick, heart rate, and rectal temperature responses in conscious, unrestrained male rats were studied. In the acute experiment unidirectional, dose-dependent analgesic, hypothermic, and negative chronotropic cardiac effects were observed within the dose range employed. Of the three variables, heart-rate decreases were most sensitive to the effects of THC, reaching significance at 2 mg/kg. Rapid development of tolerance occurred for all three measures, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Beyond the CBD and THC values represented it is important to note that due to the extensive nature of our testing we can confirm that there were no other forms of THC represented in any of the products (Δ8-THC or exo-THC) that can still impart psychotropic properties. 21 Other cannabinoids of interest that may have implications in neurology and inflammation are CBC, CBG and CBN which could not be found in over 50% of products. In products that did contain some of these cannabinoids the concentrations were less than 1 mg/ mL or gram on average with concentrations at high as 1.6 mg/mL in an occasional product.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the CBD and THC values represented it is important to note that due to the extensive nature of our testing we can confirm that there were no other forms of THC represented in any of the products (Δ8-THC or exo-THC) that can still impart psychotropic properties. 21 Other cannabinoids of interest that may have implications in neurology and inflammation are CBC, CBG and CBN which could not be found in over 50% of products. In products that did contain some of these cannabinoids the concentrations were less than 1 mg/ mL or gram on average with concentrations at high as 1.6 mg/mL in an occasional product.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators used brain levels of 5-H1AA as an indicator of changes in serotonin release. On the other hand, Mine et al (8) reported doserelated hypothermia, analgesia and negative chronotropic effects which were unidirectional following i.p. administration of THC at 0 .1 -10.0 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Excess sodium hydride was added to indole (33), which was subsequently alkylated with the appropriate bromoalkane, and then treated with trifluoroacetic anhydride to give the corresponding N-alkyl-3-(trifluoroacetyl)indole (34)(35)(36) in a one-pot process. Alkaline hydrolysis induced fluoroform elimination, 29 Indole SCs derived from L-valinamide (13,15,17) were recrystallized from isopropanol to analytical purity, while those comprising L-tert-leucinamide (14,16,18) were purified by flash chromatography owing to their superior solubility in a range of alcoholic solvents.…”
mentioning
confidence: 99%
“…[30][31][32] Cannabinoids are known to induce hypothermia and bradycardia in rats, effects that are common to phytocannabinoids like ∆ 9 -THC and heteroaromatic SCs such as JWH-018. [33][34][35] We have previously evaluated the hypothermic and bradycardic potencies of ∆ 9 -THC and numerous structurally diverse SCs including JWH-018, AM-2201, UR-144, XLR-11, PB-22, 5F-PB-22, APICA, and STS-135. 14,36 The cannabimimetic activities AB-FUBINACA and AB-PINACA were evaluated using radiotelemetry in male Wistar rats, and the effects of these SCs on body temperature ( Fig.…”
mentioning
confidence: 99%